Aquatic communities in arid landscapes: local conditions, dispersal traits and landscape configuration determine local biodiversity. Issue 10 (24th May 2015) - Morán‐Ordóñez, Alejandra; Pavlova, Alexandra; Pinder, Adrian M.; Sim, Lien; Sunnucks, Paul; Thompson, Ross M.; Davis, Jenny; Diez, Jeffrey
Abstract Aim To understand how environmental conditions and landscape structure interact at different spatial scales to shape the community composition of arid zone aquatic invertebrates with different dispersal abilities. Location Australia. Methods For each of five drainage basins and for their encompassing region (Pilbara), we built matrices of dissimilarities in presence–absence patterns of aquatic invertebrate community composition. This was carried out for all taxa collectively and separately for five dispersal trait groups: obligate aquatics, passive aerial dispersers, animals moving by aerial phoresy, weak and strong fliers. We analysed correlations between community dissimilarities and (1) dissimilarities in local environmental conditions, (2) geographic distances and (3) landscape resistance distances among the sites from which invertebrates were sampled. Calculation of landscape resistances accounted for longitudinal connectivity along the river channels (least‐cost‐path), lateral connectivity between streams and the potential effects of rugged topography on invertebrate dispersal. Results Local environmental factors and landscape resistances explained differences in community composition at the regional scale. In basins with complex topography, local environmental conditions were the main factor explaining community dissimilarities in most dispersal groups. Conversely, in basins where flatter topography meant that moderate to high lateral connectivity between streams is possible, the spatial configuration of the dendritic network determined the community composition of most dispersal trait groups. Geographic and least‐cost‐path distances were poor predictors of community composition. None of the groups showed a consistent correlation with environmental factors alone, or just landscape resistances, across all basins. Main conclusions Local environmental conditions, hydrological connectivity and landscape resistance to dispersal are all important influences on community composition of arid zone aquatic invertebrates. The impact of each of these factors varies with dispersal trait group and spatial configuration of basins: the importance of lateral connectivity for explaining a substantial proportion of community composition points to a major role of flooding regimes in maintaining biological communities.